AGENCY COST OF CREDIT ON MICROFINANCE INSTITUTIONS OF COOPERATIVE AND RURAL BANK TYPE - Purwanto Purwanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Historically, most microfinance providers are in the form of cooperatives, while some policies studies recommend shareholders ownership because it can reduce the risk of capital costs and charges opportunism manager. This study aims to analyze the factors in the cost of ownership that distinguishes MFI with the type of cooperative ownership and village banks. The study was conducted by using secondary data from the MIX (Microfinance Information Exchange) market year 2007-2013. The factors Influencing the determinants of MFI ownership costs were Analyzed using multiple logistic regression analysis technique. The study found that the MFI of cooperative has advantages in operational efficiency and credit risk while village banks have advantages in the cost of customer service, cost of debt, cost of capital, social performance and financial performance.